Flogging Freakery: Manix Abrera’s Kikomachine and Humor and Everyday Life in Philippine Youth Culture - Ancheta, Maria Rhodora G. (Humanities Diliman: A Philippine Journal of Humanities; Vol 17 No 2 (2020), 2021)
This paper examines youth culture in the Philippine context by way of Manix Abrera’s nonconformist academics in the college-themed strip Kikomachine. Abrera’s Kikomachine is the Philippines’ current comic narrative that specializes in the depiction of youth within Filipino life and culture, and the visual texts in it are seen as a successful presentation of how humor is activated as a way for young people to craft youth identity/ies within a university/study milieu. This paper will discuss how, in these comic strips’ narratives, visual structuring, and intertextual codes, the deployment of the humor of incongruity, of the carnivalesque, the use of linguistic humor, and the comic reframing of the rhetorics of shared purposes and familiar traditions, serve to redefine the functions and operations of youth communities in the Philippines. This paper posits that Abrera’s comic strip Kikomachine documents the way youth culture/subculture carves strategic positions of resistance and spaces of negotiation and “practice nonnormative actions,” looking at the ways by which the guises of humor show how Filipino youth culture within the university reclassifies and defamiliarizes the “taken-for-granted-ness” of the Filipino lived experience in everyday life.
Keywords: youth, youth culture, everyday life, Manix Abrera, Kikomachine, humor and incongruity, semantic distancing